Leadership Styles and Organizational Readiness in the Era of Digital Transformation: A Narrative Review - Siswadhi, Ferry; Karimi, Kasman; Kurdi, Moh; Widyastuti, Endang; Koesmariadi, Fransiska Agustina (Indonesian Scientific Publication, 2025)
Digital transformation is now a strategic necessity for organizations across various sectors. This review explores how different leadership styles—transformational, agile, servant, inclusive, and ethical—affect organizational readiness to adopt digital technologies. Using systematic review methods and bibliometric analysis, studies from major databases such as Scopus, Web of Science, and Google Scholar were analyzed to identify patterns and key findings. Inclusion criteria emphasized peer-reviewed research published between 2010 and 2025, encompassing diverse sectors and global contexts. Findings show that transformational leadership improves innovation and agility, agile leadership accelerates technology adoption, servant and inclusive leadership increase employee engagement and reduce resistance, while ethical leadership strengthens trust, fairness, and sustainability. Organizational readiness is also shaped by systemic factors such as regulations, culture, and resources. Developing countries often face challenges due to limited infrastructure, while developed countries benefit from stronger policy and technological support. These dynamics underscore the interdependence of leadership and systemic environments in shaping digital outcomes. In conclusion, leadership styles are decisive in shaping digital readiness, but their effects differ by sector and region. Policy support, leadership training, and organizational reforms are needed to overcome barriers and achieve inclusive digital transformation. Future research should focus on long-term impacts, contextual variations, and integrative leadership frameworks to ensure sustainable and inclusive digital transformation.